The thermolytic behaviour of hexa-1,5-diene-units incorporated in a stellane and twistbrendane skeleton: a quest for a stepwise Cope rearrangement - Lange, Holger; Löb, Patrick; Herb, Thilo; Gleiter, Rolf (Perkin, 2000)
The thermolytic behaviour of the tricyclo[3.3.0.03,7]octane (stellane) derivatives 11-13 as well as the tricyclo[4.3.0.03,8]nonane (twistbrendane) derivatives 14 and 15 have been investigated in d8-toluene. All five compounds undergo Cope rearrangements to the tricyclic systems 16-20. By means of 1H NMR spectroscopy the kinetics of these reactions have been studied at different temperatures. The lowest activation energies were encountered for the reactions of 12 and 13 (27.0 and 26.3 kcal mol−1, respectively). Model calculations on the RHF and CASSCF level and beyond (CASPT2N/6-31G*//RHF/6-31G*; CASPT2N/6-31G*//CASSCF/6-31G*) were performed for the rearrangements of 11→16, 13→18, and 27→28. These calculations reveal that the activation energies for the two-step pathway and the concerted pathway are very similar. In the case of 11 and 27 the two step mechanism via a bisallylic diradical intermediate is predicted to be slightly preferred.
Gesehen am 03.11.2020